'Five hours to sort out your life': qualitative study of the experiences of university students who access mental health support. Issue 4 (24th July 2021) - Barnett, Phoebe; Arundell, Laura-Louise; Matthews, Hannah; Saunders, Rob; Pilling, Stephen
Abstract : Background: Previous qualitative research suggests that university students feel that current service provision does not meet their needs. Exploring the reasons for this may help to promote service change, encourage the uptake of care, improve outcomes and increase satisfaction within university services. Aims: This study aimed to improve the understanding of how students experience the process of accessing and using mental health support, barriers and facilitators to treatment, and how students would adapt provision to improve experiences. Method: Semi-structured interviews were conducted with 16 full-time students who had used mental health services at university. Data were analysed using thematic analysis. Results: Five higher-order themes were identified: personalisation and informed choice, simplifying the process, feeling abandoned ignored or invisible, stigma, and superiority of private and external services. Sixteen subthemes were identified within these themes. Conclusions: Findings indicate that access to mental health support should be simplified, with collaboration across university and external health and care services, to prevent students feeling lost or abandoned when seeking care. An inclusive approach to support access and provision of services for all presentations of mental health problems should be developed.